If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = x(x + -1) Reorder the terms: 5 + 3x = x(x + -1) Reorder the terms: 5 + 3x = x(-1 + x) 5 + 3x = (-1 * x + x * x) 5 + 3x = (-1x + x2) Solving 5 + 3x = -1x + x2 Solving for variable 'x'. Combine like terms: 3x + x = 4x 5 + 4x + -1x2 = -1x + x2 + x + -1x2 Reorder the terms: 5 + 4x + -1x2 = -1x + x + x2 + -1x2 Combine like terms: -1x + x = 0 5 + 4x + -1x2 = 0 + x2 + -1x2 5 + 4x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 5 + 4x + -1x2 = 0 Factor a trinomial. (5 + -1x)(1 + x) = 0Subproblem 1
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {5, -1}
| X^2-5x+5=2x^2+7x+6 | | (2x^3y^3/2)/(x^-.5y^2)^-2 | | y=3sinx-4cos^3x | | 4a+b+4c=9 | | X^2-5=2x^2+7x+6 | | (-27/64)^-2/3 | | n+18+2n=90 | | S=bx-bc+cx | | ((2m^3*n^5)/(4n^3))^4 | | (27x)^(2/3)(3x^(6/5)) | | 5v/9=10 | | 7/2w=42 | | Y=-8+27X+20X^2 | | f(x)=7x/3x-9 | | Y=20X^2+27X-8 | | 7+7x=4(5x+2)-1 | | x+a=a+1 | | 140+2x=-120-11x | | Y=9x^2-9x+2 | | 5a-4=3a+36 | | 2X+25=X+32 | | 7a+7a^2+14b^2= | | x^2+(4k-8)*x-16=0 | | 2n+4=30 | | 3x+3(x-8)=6x-2(x-10) | | x+1=2a-2 | | 6(y+8)-8y=32 | | -4+10+2x=10 | | 8x+14=8x-7 | | 8x-14=8x-7 | | -24x-4y=-12 | | u+4u=15 |